Nā maññʻ rveʺ naññʻʺ nhaṅʻʹ maṅgalā ʼa khā peʺ naññʻʺ kyamʻʺ - Khyin, Cha rā krīʺ (Khyamʻʺ sā Cā pe Lupʻ ṅanʻʺ, 1986)
Astrological considerations for naming Burmese children and determining auspicious time.